On the effect of intermetallics on the electrical and thermal contact resistances thermoelectric material - metal - Gorskyi, P.V. (Journal of Thermoelectricity, 2019)
It is shown that the electrical and thermal contact resistances thermoelectric material (TEM) - metal in structures with anti-diffusion layers increase significantly, if transient contact layer consists of a sublayer of intermetallic and a sublayer of TEM-intermetallic composite. In a couple of bismuth telluride-nickel, NiTe2 is a dominant intermetallic. With a total thickness of transient layer of bismuth telluride-nickel ditelluride of 40 μm its electrical resistance will vary in the range from 1.28·10-6 to 3.46·10-6 Оhm·сm2, and thermal –in the range from 0.131 to 0.195 K·cm2/W. Over time, this layer can grow and, for instance, with a total thickness of 200 μm its electrical contact resistance will vary in the same temperature range from 6.40·10-6 to 1.73·10-5 Оhm·сm2, and thermal – in the range from 0.655 to 0.975 K · cm2 /W. This growth significantly affects not only the consumer characteristics, but also the reliability, life and durability of thermoelectric energy converters. In addition, it is shown that nickel ditelluride - bismuth telluride composite is not a highly efficient thermoelectric material, but the dimensionless thermoelectric figure of merit of the bismuth telluride - high-conductivity metal clusters can become significantly higher. The boundary thermoelectric figure of merit of such a composite was found. Bibl. 9, Fig. 5.